Situation Report: Hungary, 21 July 1970 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Joint Enterprise - Co-operation at Its Best First Trade Enterprise Set up in Heves County Increased Buying of Machinery from the West Imports of Goods for the Consumer Problems of Tourism Beginning of Summer University Courses Beat Mass in Baja Increased Credit for Private Plot Livestock Farmers Free Marketing of Fodder Successful Deputy Minister of Agriculture and Food Visits Britain Increasing the Co-operative Movement's Contacts with the West